PHILOSOPHICAL AND THEOLOGICAL METHODOLOGY OF D. B. HART - Hennadii Khrystokin ("Scientific Information Agency "Science-technologies-information" LLC, 2020)
Philosophy for Hart, is a continuation of theology in another way, it is a self-denial of theology, which is carried out by the European tradition to find itself. All philosophy and all its problems are a search for solutions to theological problems. For Hart, as for Balthazar, theology is thinking about being and its properties. The task of the thinker is to create a theological language, an alternative to the rhetoric of postmodernism. Theology is a language that is both a theory and a discourse. Hart's theological reflections combine the hermeneutics of texts with metaphysical reflections on meanings that make sense of a religious narrative. Hart tries to overcome metaphysics in theology, wants to think after metaphysics, to create theology after "after the death of God".